Limit of Detection Test on Salmonella spp testing on Processed Food Products Egg Pindang According to ISO 16140-3: 2021 - Eni Cahyaningsih; Aditya Anugerah Marusaha Sitorus; Alfi Sophian (Keluwih: Jurnal Sains dan Teknologi, 2023)
Abstract—The development of pathogenic bacteria detection methods in food products has led to the emergence of faster, shorter, and more efficient techniques. However, when choosing a reference method for testing, it is crucial to ensure its reliability. The purpose of this study was to determine the limit of detection (LOD) for Salmonella testing in processed chicken egg food products (Pindang Egg). The research aims to provide valuable information and serve as a reference for similar studies. The method used in this study follows ISO 6579-1:2017, while the detection limit is determined according to ISO 16140-3:2021. The results from observations on pre-enrichment and enrichment media showed that all inoculated samples exhibited a color change to cloudy, indicating bacterial growth in the media. Isolation on selective media and conformational tests confirmed 100% positivity for all samples in contamination variations of 11, 3.67, and 1.22. However, for contamination variation of 0.41, only 75% of the analyzed test data detected the presence of Salmonella, with 1 out of 4 replications not detecting it (approximately 20% failure rate). In conclusion, the lowest LOD value that can be reliably detected is 100% in the contamination variation of 1.22, while for the 0.41 variation, the detection rate only reaches 75% of the analyzed test data. Keywords: bacteria, eggs, pathogen, salmonella Abstrak—Pengembangan metode deteksi bakteri patogen dalam produk pangan telah menghasilkan teknik yang lebih cepat, lebih singkat, dan lebih efisien. Namun, saat memilih metode referensi untuk pengujian, sangat penting untuk memastikan kehandalannya. Tujuan dari penelitian ini adalah untuk menentukan batas deteksi (LOD) untuk pengujian Salmonella dalam produk pangan telur ayam olahan (Pindang Egg). Penelitian ini bertujuan untuk memberikan informasi berharga dan menjadi referensi untuk penelitian serupa. Metode yang digunakan dalam penelitian ini mengikuti ISO 6579-1:2017, sementara batas deteksinya ditentukan sesuai dengan ISO 16140-3:2021. Hasil pengamatan pada media pra-pemupukan dan pemupukan menunjukkan bahwa semua sampel yang diinokulasi menunjukkan perubahan warna menjadi keruh, menandakan pertumbuhan bakteri dalam media. Isolasi pada media selektif dan uji konformasi mengkonfirmasi positivitas 100% untuk semua sampel dalam variasi kontaminasi sebesar 11, 3,67, dan 1,22. Namun, untuk variasi kontaminasi sebesar 0,41, hanya 75% data uji yang dianalisis mendeteksi keberadaan Salmonella, dengan 1 dari 4 replikasi tidak mendeteksinya (sekitar 20% tingkat kegagalan). Sebagai kesimpulan, nilai LOD terendah yang dapat dideteksi dengan handal adalah 100% dalam variasi kontaminasi sebesar 1,22, sementara untuk variasi 0,41, tingkat deteksinya hanya mencapai 75% dari data uji yang dianalisis. Kata kunci: bakteri, telur, patogen, salmonella